2013
DOI: 10.1111/febs.12410
|View full text |Cite
|
Sign up to set email alerts
|

Morphological restriction of human coronary artery endothelial cells substantially impacts global gene expression patterns

Abstract: Alterations in cell shape have been shown to modulate chromatin condensation and cell lineage specification; however, the mechanisms controlling these processes are largely unknown. Because endothelial cells experience cyclic mechanical changes from blood flow during normal physiological processes and disrupted mechanical changes as a result of abnormal blood flow, cell shape deformation and loss of polarization during coronary artery disease, we aimed to determine how morphological restriction affects global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Interestingly, O'Connor et al have reported a shape factor-dependent regulation of the SRF target TGF-β in epithelial cells under similar, although not completely identical, experimental conditions (O'Connor and Gomez, 2013). On the other hand, a global analysis of gene expression patterns performed by Stiles et al has demonstrated that spatial confinement per se, but not a particular cell shape, is the master regulator of an adapted transcriptional profile in human coronary artery endothelial cells (Stiles et al, 2013). Since our observations in HUVECs point in a similar direction, there might be cell-or at least tissue-specific differences regarding the impact of cell shape on transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, O'Connor et al have reported a shape factor-dependent regulation of the SRF target TGF-β in epithelial cells under similar, although not completely identical, experimental conditions (O'Connor and Gomez, 2013). On the other hand, a global analysis of gene expression patterns performed by Stiles et al has demonstrated that spatial confinement per se, but not a particular cell shape, is the master regulator of an adapted transcriptional profile in human coronary artery endothelial cells (Stiles et al, 2013). Since our observations in HUVECs point in a similar direction, there might be cell-or at least tissue-specific differences regarding the impact of cell shape on transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the cell shape varied and associated with cell cytoskeleton and nuclei remodeling as a result of the morphological restriction by micropatterns. It has been widely reported that the remodeling of cell cytoskeleton and nuclei plays a significant role in the regulation of cellular differentiation, as the coupling cytoskeletal/nuclear alterations could modulate the chromosomal architecture and dynamic positioning in the nuclear space, which will regulate the subsequent accession of transcription factors to their target genes. , …”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that the remodeling of cell cytoskeleton and nuclei plays a significant role in the regulation of cellular differentiation, as the coupling cytoskeletal/nuclear alterations could modulate the chromosomal architecture and dynamic positioning in the nuclear space, which will regulate the subsequent accession of transcription factors to their target genes. 41,42 To further elucidate how the micropatterns affect the shapes and angiogenesis-related gene expression of cells, quantitative analysis of the body elongation of HUVECs in different local regions with special microstructures in scaffolds was conducted. As the lower shape index means higher elongation of cell bodies, 29 our results suggest that the cell elongation in the regions with suspended aligned nanofibers between the embossments of patterned scaffolds is more distinct than that in other regions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications from our lab and others have provided evidence that modulation of cell shape and cytoskeletal dynamics plays a major role in regulating key endothelial processes. For instance, manipulation of endothelial cell shape and actin organization results in gene expression alterations of approximately 8% of the global genome potentially through altering chromosomal boundaries within the nucleus [ 71 , 72 ]. Specific disruption of the activity of the cell shape regulators RhoA and ROCK in endothelial cells blocks a number of developmental and cellular properties such as angiogenesis, vascular formation during embryogenesis, and lung capillary development [ 39 , 42 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%